Studi Partisipasi Mahasiswa Unwira Menabung Sampah di Bank Sampah Mutiara Timor Kota Kupang - Sanggo, Maria Eusebia De Vercelli; Dhiu, Maria Rosamistika; Bunga, Fransiska Enjeline (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to determine the level of student participation in the waste bank program, factors that influence participation, and student knowledge about waste banks. Data were collected through a survey of 80 students of the Faculty of Economics and Business (FEB) and analyzed using descriptive qualitative methods. The results showed that 75.3% of students have used waste bank services and 58% regularly sort waste. Factors that influence participation include financial incentives provided (87.3%) and campus environment support (94.9%). In addition, 92.4% of students realized the positive impact of waste banks on the environment. This study also found that most students understand the types of waste accepted by waste banks (83.5%) and how they work (58.2%). Limitations of this study include limited time, distance, and limited number of respondents. Future research is recommended to involve a larger number of respondents. Other variables such as waste management and the environmental impact of participation should be added.